2022
DOI: 10.3389/fphar.2022.794528
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Approach Based on Network Analysis Combined With Experimental Verification Reveals PI3K/Akt/Nrf2 Signaling Is an Important Way for the Anti-Myocardial Ischemia Activity of Yi-Qi-Tong-Luo Capsule

Abstract: Background:Yiqi-Tongluo Capsule (YTC) is a Chinese traditional patent medicine that has been used in the treatment of myocardial ischemia (MI). However, its molecular mechanisms against MI have not been clear.Methods: Network analysis and experimental verification were used to explore the potential molecular mechanisms of YTC for MI treatment. Firstly, the main components in the capsules and the potential targets of these components were predicted by online databases. The MI related genes were collected from G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…In recent years, the protective role of Nrf2 in renal diseases has been increasingly investigated, and activation of Nrf2 can improve the antioxidant and anti-inflammatory capacity of the body, thereby reducing cell or tissue damage. 34 , 35 The AKT/Nrf2 signaling pathway is related to anti-oxidative stress 36 , 37 and is a promising target for IgA nephropathy. 38 In our present study, we found that artemisinin reduced ROS and extracellular matrix production in an LPS-induced inflammatory environment, which is consistent with Sun et al’s study.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the protective role of Nrf2 in renal diseases has been increasingly investigated, and activation of Nrf2 can improve the antioxidant and anti-inflammatory capacity of the body, thereby reducing cell or tissue damage. 34 , 35 The AKT/Nrf2 signaling pathway is related to anti-oxidative stress 36 , 37 and is a promising target for IgA nephropathy. 38 In our present study, we found that artemisinin reduced ROS and extracellular matrix production in an LPS-induced inflammatory environment, which is consistent with Sun et al’s study.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the activation of the PI3K/AKT signalling pathway can affect the survival, proliferation and apoptosis of cardiomyocytes, the energy metabolism and regulation of cardiomyocytes, and the regeneration of blood vessels, which is closely related to the regulation of cardiomyocyte function [ 58 ]. A recent study showed that Yiqi-Tongluo capsules might alleviate myocardial ischaemia by increasing the phosphorylation of PI3K, Akt and Bcl-2 and decreasing the expression of cleaved caspase-3 and Bax [ 59 ]. Polygonum cuspidatum exerts a potent antihyperlipidaemic effect by activating the PI3K/AKT signalling pathway [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacodynamic and protein-expression experiments revealed that the ardisiacrispin B reduced AKT-, P-AKT-, PI3K-, and P-PI3K-protein expression in LPS-induced RAW264.7. In the growth-factor superfamily, PI3K is an important signal-transduction molecule, and AKT is a serine/threonine kinase, which is a key mediator of PI3K-mediated signal transduc-tion [56,57]. The phosphorylation of its serine and threonine residues activates AKT with the help of PI3K-dependent kinase (PDK).…”
Section: Discussionmentioning
confidence: 99%